Associations between non-anaemic iron deficiency and outcomes following surgery for colorectal cancer: An exploratory study of outcomes relevant to prospective observational studies. Issue 2 (March 2019) - Miles, Lachlan F; Sandhu, Ravinder NS; Grobler, Anneke C; Heritier, Stephane; Burgess, Adele; Burbury, Kate L; Story, David A
Iron deficiency is common in colorectal cancer. Despite perioperative guidelines advocating for the correction of non-anaemic iron deficiency prior to major surgery, the impact of this pathology on postoperative outcome is unclear. We conducted a single-centre, historical cohort study of 141 elective resections for colorectal cancer. We stratified non-anaemic patients into iron deficient and iron replete groups, and collected data on baseline characteristics, preoperative laboratory results, intraoperative events and postoperative outcomes. As this study was an exploratory work for future research, a P -value of 0.25 was considered relevant. Patients in the deficient group demonstrated lower baseline ferritin (median (interquartile range, IQR) 76 (41–141) µg/L versus 207 (140–334) µg/L, P  < 0.001) and transferrin saturation (mean (standard deviation, SD) 18% (8%) versus 32% (12%), P  < 0.001) than those in the replete group, and lower starting haemoglobin (mean (SD) 138 (10) g/L versus 144 (12) g/L, P  = 0.01). The deficient group had increased re-admission (25% (24%) versus 4% (11%), P  = 0.15) and all-cause infection (25% (24%) versus 5% (14%), P  = 0.24). A decrease of two days in days alive and out of hospital at postoperative day 90 was seen in the deficient group on univariate analysis (median (IQR) 81 (75–84) versus 83 (78–84), P  = 0.25). This reduced to 1.24 days in multivariate adjusted quantile regression analysis ( P  = 0.22). Days alive and out of hospital at day 90, postoperative re-admission and postoperative infection may be meaningful outcome measures for future prospective observational work examining non-anaemic iron deficiency in patients undergoing major surgery for colorectal cancer.